More than the sum of the parts: Toward full‐length receptor tyrosine kinase structures. Issue 6 (2nd May 2019) - Diwanji, Devan; Thaker, Tarjani; Jura, Natalia
Abstract: Intercellular communication governs complex physiological processes ranging from growth and development to the maintenance of cellular and organ homeostasis. In nearly all metazoans, receptor tyrosine kinases (RTKs) are central players in these diverse and fundamental signaling processes. Aberrant RTK signaling is at the root of many developmental diseases and cancers and it remains a key focus of targeted therapies, several of which have achieved considerable success in patients. These therapeutic advances in targeting RTKs have been propelled by numerous genetic, biochemical, and structural studies detailing the functions and molecular mechanisms of regulation and activation of RTKs. The latter in particular have proven to be instrumental for the development of new drugs, selective targeting of mutant forms of RTKs found in disease, and counteracting ensuing drug resistance. However, to this day, such studies have not yet yielded high‐resolution structures of intact RTKs that encompass the extracellular and intracellular domains and the connecting membrane‐spanning transmembrane domain. Technically challenging to obtain, these structures are instrumental to complete our understanding of the mechanisms by which RTKs are activated by extracellular ligands and of the effect of pathological mutations that do not directly reside in the catalytic sites of tyrosine kinase domains. In this review, we focus on the recent progress toward obtaining such structures and the insights already gained by structural studies of the subdomains of the receptors that belong to the epidermal growth factor receptor, insulin receptor, and platelet‐derived growth factor receptor RTK families. © 2019 IUBMB Life, 71(6):706–720, 2019